Spot-test identification and rapid quantitative sequential analysis of dipyrone - Tubino, Matthieu; Biondo, Adriane Cristina; Vila, Marta Maria Duarte Carvalho; Pezza, Leonardo; Pezza, Helena Redigolo (Eclética Química, 2010)
A qualitative spot-test and tandem quantitative analysis of dipyrone in the bulk drug and in pharmaceutical preparations is proposed. The formation of a reddish-violet color indicates a positive result. In sequence a quantitative procedure can be performed in the same flask. The quantitative results obtained were statistically compared with those obtained with the method indicated by the Brazilian Pharmacopoeia, using the Student’s t and the F tests. Considering the concentration in a 100 μL aliquot, the qualitative visual limit of detection is about 5×10-6 g; instrumental LOD ≅ 1.4×10-4 mol L-1 ; LOQ ≅ 4.5×10-4 mol L-1.